2013
DOI: 10.1071/sr12374
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the allocation of soil organic carbon to biologically significant fractions

Abstract: Soil organic carbon (OC) exists as a diverse mixture of organic materials with different susceptibilities to biological decomposition. Computer simulation models constructed to predict the dynamics of soil OC have dealt with this diversity using a series of conceptual pools differentiated from one another by the magnitude of their respective decomposition rate constants. Research has now shown that the conceptual pools can be replaced by measureable fractions of soil OC separated on the basis of physical and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 27 publications
2
90
0
Order By: Relevance
“…The HF procedure resulted in an average C loss of 17.4 %. Operating conditions were identical to those reported in Baldock et al (2013a). In order to quantify absolute differences in chemical composition, data were reported by normalizing the recorded signal intensity by the amount of observable C, determined following the conventions of Smernik and Oades (2000), in the analyzed sample.…”
Section: Soil Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The HF procedure resulted in an average C loss of 17.4 %. Operating conditions were identical to those reported in Baldock et al (2013a). In order to quantify absolute differences in chemical composition, data were reported by normalizing the recorded signal intensity by the amount of observable C, determined following the conventions of Smernik and Oades (2000), in the analyzed sample.…”
Section: Soil Analysesmentioning
confidence: 99%
“…Mid-infrared spectroscopy in combination with partial least-squares regression (MIR-PLSR) was used to estimate the distribution of OC into three biologically meaningful pools, the particulate (POC), humus (HOC), and resistant (ROC) organic carbon fractions (Baldock et al, 2013a, b), using the Unscrambler X software package (CAMO Software, Oslo, Norway). Prediction statistics (Hotelling's T square and Mahalanobis distance) suggested that this soil type was well represented in the calibration set of Baldock et al (2013b).…”
Section: Soil Analysesmentioning
confidence: 99%
“…Spectra were compared to a glycine standard for observability. For these NMR analyses, 10-20,000 scans were collected per sample, and the collected spectra were integrated into eight regions: 0-45 ppm (Alkyl), [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] For the samples from erosional sites, the Soil Carbon Research Program (SCaRP) MIR-PLSR model was used to predict three organic C fractions within the soil samples: resistant organic carbon (ROC, particles that are chemically similar to charcoal, or PyC), particulate organic carbon (POC, particles 50-2,000 µm excluding PyC), and humic organic carbon (HOC, particles <50 µm excluding PyC) (Baldock et al, 2014). This model has proven to be a reliable and time-effective method for predicting soil fractions and has been demonstrated a reasonable predictor across different land uses and vegetation types in and out of Australia (Baldock et al, 2013b;Ahmed et al, 2017;Jauss et al, 2017).…”
Section: Spectroscopymentioning
confidence: 99%
“…Residue samples were treated with 2 % hydrofluoric acid (HF) according to the method of Skjemstad et al (1994) to remove paramagnetic materials and concentrate organic C for 13 C NMR analyses. Cross-polarisation 13 C NMR spectra were acquired using a 200 MHz Avance spectrometer (Bruker Corporation, Billerica, MA, USA) following the instrument specifications, experimental procedures and spectral processing outlined by Baldock et al (2013b). …”
Section: C Nmrmentioning
confidence: 99%